Soft skills the matchless traits and skills in nursing practice: An integrative review - Luke Laari; Oboshie Anim-Boamah; Christian Makafui Boso (Tehran University of Medical Sciences, 2022)
Background & Aim: While hard skills refer to the technical ability and factual knowledge needed to do a job, soft skills allow you to use your technical abilities and knowledge more effectively. These two skills are complementary, but soft skills are prerequisites in every profession where human interaction and teamwork are needed to succeed. This integrative review examined the research on soft skills in nursing and made recommendations based on its findings. Methods & Materials: Whittemore and Knafl's five-step integrative review framework was carried out using four electronic databases. These databases are the Cumulative Index to Nursing & Allied Health Literature (CINAHL), PubMed, Medline on EBSCOhost, and Scopus. Searches were conducted using keywords: soft skills, non-technical skills, nursing skills, nursing art, and aesthetics. The literature search explored no date ranges, and only the English language was considered. Full texts of relevant studies in both qualitative and quantitative research were retrieved. Critical appraisal was undertaken, and the findings of the relevant studies were analyzed using thematic analysis. Results: Seventeen studies were included, and the findings suggest an urgent need for soft skills in the nursing domain. Five themes emerged: the meaning of soft skills in nursing, the benefits of soft skills in nursing; the need for soft skills in nursing; the incorporation of soft skills into nursing practice; and the relationship between hard and soft skills. Findings show soft skills are the cognitive and social capabilities that complete the technical skills of the nurse. Conclusion: Incorporating soft skills into the nursing curriculum should be a resuscitative call that requires immediate attention.